Recent advances in breeding maize for resistance to Striga hermonthica (Del.) Benth - Menkir, A.; Kling, J.G.; Badu-Apraku, Baffour; The, C.; Ibikunle, O. (2002)
Striga represents the largest biological threat to cereal production in sub-Saharan Africa. Breeding for resistance to Striga has been the focal point of IITA to reduce the impact of this parasite on maize production. The early breeding work at IITA focused on search for tolerance to Striga. IITA has made a significant shift in emphasis towards selection of resistant maize genotypes that support a reduced number of Striga plants since the early 1990s. Population improvement and the inbred-hybrid method have been used to increase the resistance to Striga. An experiment was conducted to evaluate from the five cylces of recurrent selection in a late maturing composite, TZL COMP. 1-W, at two locations for two years. Selection reduced Striga damage symptoms by 3% per cycle and number of emerged Striga plants by 10% per cycle.At the same time, grain yield in this population increased by 16% per cycle under Striga infestation and by 2% per cycle under non-infested conditions. Furthermore, several open pollinated varieties of different maturity with good levels of resistance to Striga were derived from diverse populations. The inbred-hybrid approach has also been effective in identifying the inbred lines with high levels of resistance to Striga from diverse sources of germplasm. Some of these lines were evaluated in hybrid combinations at two locations with and without Striga infestation. Most of the hybrids involving these inbred lines supported fewer Stiga plants and produced higher yields under infestation with Striga than a commercial hybrid. The best hybrids were also more productive than a standard Striga resistant hybrid check with much fewer emerged Striga plants. Theses hybrids sustained little or no yield loss under infestation with S. hermonthica. In contrast to tolerance, the selection and use of such resistant open-pollinated varieties and hybrids can reduce reproduction of seed of the parasite thereby depleting the soil innoculum in areas where the parasite is endemic.